2020
DOI: 10.1186/s41936-020-00163-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological description of the digestive canal in Taeniopygia guttata (zebra finch) and Sturnus vulgaris (starling)

Abstract: Background The present study is designed to identify the morphological description of the digestive tract in two species of different birds; these birds were Taeniopygia guttata (zebra finch) which is granivorous and Sturnus vulgaris (Starling) which is omnivorous. Results The results showed that the digestive canal of both birds was similar in the essential structure. It begins with the oropharyngeal cavity, which starts with the beak. The beak appeared different in the outer shape, which depends on the feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The esophagus in the Ring-necked parakeet was shorter and narrower than that of the Black-shouldered Kite. These results agreed with Taha and Al-Duleemy (15) in Zebra finch and Starling. The length of the esophagus is related to the size of the food intake because the long esophagus can expand more than the short esophagus.…”
Section: Discussionsupporting
confidence: 91%
“…The esophagus in the Ring-necked parakeet was shorter and narrower than that of the Black-shouldered Kite. These results agreed with Taha and Al-Duleemy (15) in Zebra finch and Starling. The length of the esophagus is related to the size of the food intake because the long esophagus can expand more than the short esophagus.…”
Section: Discussionsupporting
confidence: 91%
“…Previous investigations have been completed on the comparative morphological and anatomical changes in tongues and oral cavities of birds in relation to dietary niche, especially those fed on seeds. In this setting, much literature illustrated the structural and functional aspects of tongues in several species, sharing the same feeding preferences to that of the Eurasian collared dove, including the Egyptian laughing dove (Abumandour & El-Bakary, 2019), the rock pigeon (Abumandour & Kandyel, 2020), the domestic pigeon (Mahdy, 2020), quail (Toyoshima et al, 1993; Parchami et al, 2010), chicken (Iwasaki & Kobayashi, 1986), the house sparrow (Abumandour, 2018), zebra finch and common starling (Taha & AL-Duleemy, 2020), the chukar partridge (Sağsöz et al, 2013), and European magpie and common raven (Erdoǧan & Alan, 2012) showed particular similarities in the distribution of their mechanical papillae, the presence of papillary crest between the lingual body and root, and possessing large conical papillae at the edge of their laryngeal entrance. Still, these aforementioned species displayed some dissimilarities in their lingual microstructures, the number of mechanical and gustatory papillae, and the localization of the salivary glands in regards to their feeding styles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its ontogeny and evolutionary history are greatly affected by several factors including hygiene, vocalization, functional considerations, type of food, manipulation, and swallowing (King & McLelland, 1984; Zusi & Livezey, 2006; Igwebuike & Eze, 2010; Erdoǧan & Iwasaki, 2014; Mahdy, 2020). Emphasis on the study of different palatal structures with its ridges, specifically herbivorous birds, using gross anatomical and scanning electron microscopy (SEM) revealed that most palates are adorned with small or large caudo-medially, caudo-laterally, and caudally directed conical papillae which are discernible at the anterior and lateral palatine ridges or the caudal region surrounding the choanal or infundibular clefts of the palate (Erdoǧan & Alan, 2012; Sağsöz et al, 2013; Erdoğan & Pérez, 2015; Abumandour, 2018; Abumandour & Kandyel, 2020; Mahdy, 2020; Taha & AL-Duleemy, 2020). Contradictory, the palate of ratites including ostrich, emu, and rhea is relatively broad and the rostral 2/3 of the hard palate is nonpapillate; however, the caudal part has folded recess with short slender papillae at the boundaries of the choanal cleft (Gussekloo, 2006; Crole & Soley, 2010 a ; Tivane et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These different compartments of the gut display both morphological and functional variation between species, variation that is related to evolutionary history, dietary niche, seasonal factors, and other aspects of ecology (Ibrahim, Mokhtar, & Fadl, 2020; Liman, Alan, & Küçük Bayram, 2010; Lv et al, 2014; Smith, Grasty, Theodosiou, Tabin, & Nascone‐Yoder, 2000; Wilkinson et al, 2018). Many descriptive studies have explored the diversity of feeding systems in birds and how they relate to structural adaptation in the digestive tract (Al‐Saffar & Al‐Samawy, 2016; Hanafy, Abumandour, & Bassuoni, 2020; Kadhim, Zuki, Noordin, & Babjee, 2011; Madkour & Mohamed, 2019a, 2019b; Saran & Meshram, 2021; Senthamil, Ushakumary, & Ramesh, 2008; Taha & AL‐Duleemy, 2020; Zhu, 2015b; Zhu, Wang, Shi, Hu, & Chen, 2013). The microstructure of the digestive tract is also known to be directly relevant to its function, across multiple bird species (Aguzey, Gao, Haohao, & Guilan, 2018; Dahlke, Ribeiro, Kessler, Lima, & Maiorka, 2003; Karasov, Martínez del Rio, & Caviedes‐Vidal, 2011; Liman et al, 2010; Naderinejad et al, 2016; Smith et al, 2000; Svihus, 2014; Zaefarian, Abdollahi, & Ravindran, 2016).…”
Section: Introductionmentioning
confidence: 99%